CREB phosphorylation coincides with transient synapse formation in the rat hippocampal dentate gyrus following avoidance learning - O'Connell, C (Neural plasticity, 2000)
Spine density change in the hippocampal dentate gyrus accompanies memory consolidation and coincides with the increased expression of ribosome-rich, hyperchromatic granule cells. Although this suggests increased protein synthesis to be required for synaptic growth in the 5 to 7 h post-training period, little temporal mapping of the associated molecular mechanisms has been done. Here, we demonstrate a similar frequency of hyperchromatic cells in naïve animals and in those sacrificed 6 h post-training, suggesting a transient repression of protein synthesis in the early post-training period. Immunoblot analysis of CREB phosphorylation in the dentate gyrus supported this view, with downregulation from basal levels observed at 2 to 3 h and at 12 h post-training. Protein synthesis reactivation appears to be specific for de novo spine production as no change in spine frequency accompanies the immediate post-training period of depressed protein synthesis. These findings support the view that CREB-mediated gene transcription is a requirement for long-term memory consolidation and may be directly implicated in the process of synaptic growth